Poverty and Power: The Moral Regulation of Single Mother University Students - O'Gorman, Laurel (Journal of the Motherhood Initiative for Research and Community Involvement, 2016)
The university was designed with the traditional student in mind. Students who are sole-support parents often have difficulties negotiating their experiences and expectations as a student with those that arise as a parent. This paper uses institutional ethnographic interviews conducted in the summer and fall of 2011 with eight single mothers who are postsecondary students in order to better understand the barriers that they face while obtaining a postsecondary education. This paper explores the theme of power and moral regulation from the interviews. I begin by describing the concept of moral regulation and use this concept as a theoretical base to explore the experiences of shame, violence, scrutiny, stigma and resistance that arose throughout the interviews and in the literature.